2022
DOI: 10.1186/s12872-022-02756-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of miR-224-5p in circulating extracellular vesicles of patients with reduced coronary flow reserve

Abstract: Background Endothelial and microvascular dysfunction are pivotal causes of major adverse cardiac events predicted by coronary flow reserve (CFR). Extracellular Vesicles (EVs) have been studied extensively in the pathophysiology of coronary artery disease. However, little is known on the impact of the non-coding RNA content of EVs with respect to CFR. Methods We carried out a study among 120 patients divided by high-CFR and low-CFR to profile the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Eyyupkoca et al [ 69 ] described that eight miRNAs (miR-23b-3p, miR-26b-5p, miR-199a-5p, miR-301a-3p, miR-374a-5p, miR-423-5p, miR-483-5p, and miR-652-3p) were associated with adverse left ventricular remodeling (ALVR), although only three, miR-301a-3p, miR-374a-5p, and miR-423-5p, in a significative manner. James et al [ 71 ] performed a multiplex array profiling, demonstrating that miR-224-5p is more expressed in circulating vesicles of patients with reduced coronary flow reserve. Barbalata et al [ 33 ] concluded that plasma levels of miR-142, miR-223, and miR-155 were higher in peripheral artery disease (PAD) patients with cardiovascular events (CVEs) compared with those without CVEs, while miR-92a is lower.…”
Section: Resultsmentioning
confidence: 99%
“…Eyyupkoca et al [ 69 ] described that eight miRNAs (miR-23b-3p, miR-26b-5p, miR-199a-5p, miR-301a-3p, miR-374a-5p, miR-423-5p, miR-483-5p, and miR-652-3p) were associated with adverse left ventricular remodeling (ALVR), although only three, miR-301a-3p, miR-374a-5p, and miR-423-5p, in a significative manner. James et al [ 71 ] performed a multiplex array profiling, demonstrating that miR-224-5p is more expressed in circulating vesicles of patients with reduced coronary flow reserve. Barbalata et al [ 33 ] concluded that plasma levels of miR-142, miR-223, and miR-155 were higher in peripheral artery disease (PAD) patients with cardiovascular events (CVEs) compared with those without CVEs, while miR-92a is lower.…”
Section: Resultsmentioning
confidence: 99%
“…EV Proteomic and RNA Profiling The integration of proteomic and RNA profiling in EV research holds great potential for advancing precision medicine and improving disease diagnosis and monitoring. The development of EV proteomic profiling has been promising for the detection and monitoring of cancer, emphasizing the importance of understanding the protein cargo of EVs for clinical applications [19,148]. Through the use of high-throughput sequencing and NGS, comprehensive analyses of EV RNA content have been carried out, which have shed light on the multitude of RNA species present in EVs as well as the functional implications of their presence [130].…”
Section: Ev Isolation and Characterization Technologiesmentioning
confidence: 99%
“…However, elevated EV levels of miR-224 are not specific to RCC. miR-224 is demonstrated to function as an oncogenic miRNA in several types of cancer, including hepatocellular carcinoma, non-small-cell lung cancer, and colorectal cancer [ 122 , 123 ]. Du et al found that the miR-let-7i-5p, miR-26a-1-3p, and miR-615-3p levels in plasma EVs are associated with the overall survival (OS) of mRCC patients.…”
Section: The Potential Of Evs In Clinical Applicationmentioning
confidence: 99%